2011 18th Asia-Pacific Software Engineering Conference 2011
DOI: 10.1109/apsec.2011.37
|View full text |Cite
|
Sign up to set email alerts
|

Executable and Translatable UML -- How Difficult Can it Be?

Abstract: Model-Driven Engineering is a paradigm for software engineering where software models are the primary artefacts throughout the software life-cycle. The aim is to define suitable representations and processes that enable precise and efficient specification, development and analysis of software.Our contributions to Model-Driven Engineering are structured according to Boyer's four functions of academic activity -the scholarships of teaching, discovery, application and integration. The scholarships share a systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 75 publications
(113 reference statements)
0
7
0
Order By: Relevance
“…Executable UML is an extension of UML that allows models to be executed and translated into code via model compilers [1]. The basic elements of executable UML are class diagrams, state machine diagrams, and action languages.…”
Section: Concepts Used In This Program 31 Software Modeling Educatiomentioning
confidence: 99%
See 1 more Smart Citation
“…Executable UML is an extension of UML that allows models to be executed and translated into code via model compilers [1]. The basic elements of executable UML are class diagrams, state machine diagrams, and action languages.…”
Section: Concepts Used In This Program 31 Software Modeling Educatiomentioning
confidence: 99%
“…Executable UML is also used to model the component and class diagrams, and the state machines during the design phase, instead of UML. It has been demonstrated that executable UML can be used by novice software modelers [1]. It was also used to introduce the abstract thinking processes involved in modeling, before introducing the more concrete thought processes involved in programming with the standard textual imperative programming languages used at high school level [9].…”
Section: Introductionmentioning
confidence: 99%
“…Ericsson has previously had success in using xtUML for reuse of platform-independent models [1] and test generation [6] while still finding the tool easy enough to use by novice modellers [4]. We also know from experience that xt-UML integrates nicely with legacy code written in C. Since the models are executable it is possible for users to validate that the models have the required functionality without generating code for deployment.…”
Section: Modelling Control Using Xtumlmentioning
confidence: 99%
“…From our experience of xtUML [4] it does not take that long time to get used to the syntax of the modelling elements, as it does to get used to the tool that creates them. More importantly, as the project evolved we saw a need for handling the data flow in a way that neither xtUML nor the existing platform supported.…”
Section: The Right Language For the Right Taskmentioning
confidence: 99%
“…We therefore employed an executable modeling language that supplied the students with continuous validation [3]. Using the terminology of cognitive apprenticeship teacher-student time was used for modelling and coaching while scaffolding and exploration distinguished the work the students did on their own.…”
Section: Teaching Mdementioning
confidence: 99%